Motivations for sustained use of modern contraceptives in a peri-urban area: An analytical cross-sectional study - Seth Amponsah-Tabi; Hannah Boatemaa Asante; Edward T. Dassah; Eric Sarpong Ansong; Maxwell Kankam; Amponsah Peprah; Charles Senaya; Jude John Annan; Roderick Larsen Reindorff; Henry S. Opare-Addo (PLoS ONE, 2025)
Background Discontinuation of contraceptives is one of the most significant concerns for family planning programmes. It is estimated that 1 in 3 women who take up modern contraceptives discontinue use by the end of a year due to various reported challenges. This study aimed to determine proportion of sustained users (continual use of the same method for 2 or more years) and their motivation. Methodology A cross-sectional survey with a questionnaire was conducted among 397 women of reproductive age (15–49 years) in the Mfantseman municipality to assess the factors that motivate them to sustain the use of modern contraceptives. A multi-stage sampling technique was used to obtain the desired study participants. Results 39.8% of study participants had used their method of contraception for 2 years with 14.4% having used theirs for 4 or more years. Ever missing one’s dose of their method, birth goals and the need for privacy when using a method had the highest odds for sustained use with aORs of 3.46, 2.53 and 2.09 respectively. About 40% of the respondents reported socio-economic reasons as motivation for sustained use. Conclusion Findings from the study suggest it would be beneficial for service providers to demonstrate tolerance towards women who miss their doses or schedule of their chosen method of modern contraceptives. The intention for adopting modern contraceptive use of more than a third of the respondents was to improve their socioeconomic status.